Pusa Vaibhav: A new round purple variety of brinjal for commercial cultivation - Saha, Partha; Tomar, Bhoopal Singh; Munshi, Anilabha Das; Behera, Tusar Kanti; Lyngdoh, Yvonne Angel; Rana, SC (Indian Horticulture, 2022)
Pusa Vaibhav is a purple-coloured round fruited brinjal variety developed by hybridization (Pusa Purple Round × Br-112) followed by selection in the Division of Vegetable Science, ICAR-Indian Agricultural Research Institute, Pusa, New Delhi, India. The variety was identified for release in the XXXVII AICR P (Vegetable Crops) Group Meeting held at Tamil Nadu Agricultural University (TNAU), Coimbatore during June 22-25, 2019 for cultivation in plains of Punjab, Uttar Pradesh, Bihar and Jharkhand.